1995
DOI: 10.1016/s0741-5214(95)70246-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of carotid artery stenosis by ultrasonography, conventional angiography, and magnetic resonance angiography: Correlation with ex vivo measurement of plaque stenosis

Abstract: In general, the correlation of measurements of ex vivo stenosis with all modalities was good in these severely diseased arteries, although it was better for DUS (r = 0.80; p < 0.001) and MRA (r = 0.76; p < 0.001) than for CA (r = 0.56; p < 0.05).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0
9

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(78 citation statements)
references
References 13 publications
1
68
0
9
Order By: Relevance
“…For the supra-aortic vasculature in particular, in which stenoses often develop asymmetrically, this may result in underestimation of the narrowest portion of the residual lumen and potentially result in patients not receiving appropriate treatment. 29,30 However, this was a potential limitation only for the assessment of diagnostic performance; it would not have influenced the blinded readers' subjective assessment of CE-MRA image quality. A second possible limitation is that examinations were performed at 1.5T only.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…For the supra-aortic vasculature in particular, in which stenoses often develop asymmetrically, this may result in underestimation of the narrowest portion of the residual lumen and potentially result in patients not receiving appropriate treatment. 29,30 However, this was a potential limitation only for the assessment of diagnostic performance; it would not have influenced the blinded readers' subjective assessment of CE-MRA image quality. A second possible limitation is that examinations were performed at 1.5T only.…”
Section: Figmentioning
confidence: 99%
“…[1][2][3] Many of the included studies, however, used either a double dose of gadolinium contrast agent or a standard volume of [25][26][27][28][29][30] mL (corresponding to 0.17-0.2 mmol/kg for a 75-kg patient). Although some studies have used lower doses, this use has often been associated with compromised spatial resolution and image quality.…”
mentioning
confidence: 99%
“…In fact, preliminary data suggest that noninvasive imaging may be more sensitive than CA in some instances. 40 A comparison of CA, MRA, and DUS, with surgical specimens rather than CA used as the gold standard, 52 found that DUS and MRA each correlate better with the endarterectomy specimen than does CA. This discrepancy can be attributed to the fact that the smallest diameter is often not appreciated by CA when the stenosis is elliptical or complex in shape.…”
Section: Mra Of the Carotid Arterymentioning
confidence: 99%
“…Moreover, our model based on splines can model noncircular vessel cross sections. Although often it is assumed that vessels have a circular cross section, ex vivo measurements [28] have shown that this assumption is rather simplistic and, especially at the stenosis, a wide variety of geometric shapes can be observed. Elgersma and coworkers [29] have supported this idea based on in vivo measurements from multiple projections of 3-D rotational angiography (RA) images and concluded that this imposes a severe limitation to measurements performed on (only two or three) 2-D projections.…”
Section: Discussionmentioning
confidence: 99%
“…However, accurate quantification in these approaches is limited, since the underlying assumptions are often not valid, especially in pathological conditions [28], [29]. The fact that very few quantitative evaluation results have been reported in the literature reveals, to some extent, the difficulty of obtaining accurate measurements with purely geometry guided algorithms.…”
Section: Introductionmentioning
confidence: 99%